ENGLISH LANGUAGE NEEDS OF INDONESIAN TEACHERS IN INTERNATIONAL SCHOOLS: TOWARD THE DEVELOPMENT OF AN ESP COURSE - Rezky Atri Oktarin; Tania Syafutri; Ejontomi Afrizon; Pahrozi Ahmad (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2026)
The increasing demand for English-medium instruction in international schools has highlighted the importance of English proficiency among teachers. However, many Indonesian teachers have limited opportunities to develop professional English skills required in international educational settings. This study aims to investigate the English language needs of Indonesian teachers working in international schools and to formulate recommendations for English for Specific Purposes (ESP) course development. A descriptive quantitative design was employed. Thirty-five teachers from international schools participated in the study. Data were collected through questionnaires and semi-structured interviews. The findings revealed that speaking was the most important skill required by teachers, followed by writing, listening, and reading. The participants frequently used English for classroom instruction, classroom management, communication with parents, professional meetings, and report writing. Furthermore, teachers reported challenges in explaining complex concepts, conducting spontaneous classroom interactions, and writing formal academic reports. Based on these findings, four ESP modules are proposed, namely Classroom English, Instructional Communication, Parent-Teacher Communication, and Professional Writing. The study highlights the importance of designing ESP programs that address authentic workplace communication needs.